American Indians in the early West - Mathews, Sandra K., 1963- (Cultures in the American West series., 2008)
American Indians in the Early West offers a concise guide to the development of American Indian communities, from the first migrations through the arrival of the Spanish, French, and Russians, to the appearance of Anglo-American traders in the easternmost portions of the West around 1800. With coverage divided into periods and regions, American Indians in the Early West looks at how Indian communities evolved from hunter-gatherers to culturally recognized tribes, and examines the critical encounters of those tribes with non-Natives over the next two-and-a-half centuries. Readers will see that the issues at stake in those encounters--political control, preserving traditions, land and water rights, resistance to economic and military pressures--are very relevant to the Native American experience today.